Effect of novel recovery garments utilising nanodiamond- and nanoplatinum-coated materials (DPV576-C) on physical and psychological stress in baseball players: A randomised, placebo-controlled trial - Choi, Y.; Makita, M.; Nakamura, Y.; Yamamoto, K.; Nara, T.; Kawamura, T.; Fukuda, H.; Katano, H.; Miyakawa, S.; Maeda, S. (European Journal of Sport Science, 2019)
Based on research suggesting that nanomaterial containing nanodiamond- and nanoplatinum-coated fibres (DPV576-C) may reduce the stress response, garments to enhance athletes` recovery from training-induced stress have been manufactured. This study examined the effects of wearing recovery garments on the physical and psychological stress of Japanese male baseball players. Thirty-eight players aged 18-21 (19.6 ± 0.2 years) who participated in a two-week intensified training programme were randomly assigned to two groups: 19 wore recovery (DPV576-C) garments (RG group) and 19 wore non-recovery garments (placebo group). Both groups wore the garments overnight. Mood states, using the Profile of Mood States questionnaire, and salivary cortisol levels were measured before (day 0) and after (day 14) the training period. Saliva samples were collected from 07:00-07:30 am. Both groups` fatigue scores significantly increased after the training period (RG: 8.4 ± 0.8-10.1 ± 0.8 score; placebo: 9.8 ± 1.0-11.7 ± 1.0 score). The total mood disturbance (TMD) score increased significantly in the placebo group (21.0 ± 2.3-27.2 ± 3.0 score) but not in the RG group (17.4 ± 2.7-20.2 ± 2.2 score). Salivary cortisol concentrations decreased significantly in the RG group (0.71 ± 0.08-0.49 ± 0.05 µg/dL) but not in the placebo group (0.61 ± 0.06-0.58 ± 0.10 µg/dL). Therefore, wearing the DPV576-C garments overnight attenuated increases in TMD levels and decreased salivary cortisol levels following intensified training. DPV576-C garments may have beneficial effects on training-induced physical and psychological stress among athletes.